DEVELOPMENT OF SOCIAL SPHERES IN THE CITIES OF KASHKADARYA REGION - Safarov , I.B; Rasulov , F.I (Educational Research in Universal Sciences, 2024)
In this article, the level of development of social spheres in the cities of Kashkadarya region is studied and analyzed. Proposals and recommendations on the development of social spheres in the cities of Kashkadarya region have been developed.